Analisis Kekuatan Rangka Rak Tanaman Hidroponik Pada Smart Indoor Farming Menggunakan Software Solidworks Simulation dan Ansys Workbench - Deru Mustafa, Deru; Boni Sena, Boni Sena (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Indoor vertical farming is a method of growing plants in layers that are stacked vertically or integrated into other structures by using water as a growing medium / hydroponics. One method or hydroponic system that is often used for plant cultivation in indoor vertical farming is Nutrient Film Technique (NFT). The NFT hydroponic system is a type of hydroponics that has a method of plant cultivation where plant roots grow in a shallow and circulating layer so that plants can get enough water, nutrients and oxygen. In maximising the prevention of obstacles and challenges that occur in vertical hydroponic plant cultivation indoors, it is necessary to design an adjustable rack design as a concept or description of solutions in the form of analysis of rack comparison testing using 3D images viewed from stress, displacement and FOS (factor of safety) of the rack to determine the material and specification of the indoor vertical farming rack and further increase the efficiency value of the existing hydroponic rack system.